Theories of Social Media: Philosophical Foundations. (February 2018) - Qi, Jiayin; Monod, Emmanuel; Fang, Binxing; Deng, Shichang
Abstract: Although many different views of social media coexist in the field of information systems (IS), such theories are usually not introduced in a consistent framework based on philosophical foundations. This paper introduces the dimensions of lifeworld and consideration of others. The concept of lifeworld includes Descartes' rationality and Heidegger's historicity, and consideration of others is based on instrumentalism and Heidegger's "being-with." These philosophical foundations elaborate a framework where different archetypal theories applied to social media may be compared: Goffman's presentation of self, Bourdieu's social capital, Sartre's existential project, and Heidegger's "shared-world." While Goffman has become a frequent reference in social media, the three other references are innovative in IS research. The concepts of these four theories of social media are compared with empirical findings in IS literature. While some of these concepts match the empirical findings, some other concepts have not yet been investigated in the use of social media, suggesting future research directions.